Recoveries After Pandemics : The Role of Policies and Structural Features - Cuesta Aguirre, Juan Pablo (IMF Working Papers; Working Paper ;, 2021)
To shed light on the possible scarring effects from Covid-19, this paper studies the economic effects of five past pandemics using local projections on a sample of fifty-five countries over 1990-2019. The findings reveal that pandemics have detrimental medium-term effects on output, unemployment, poverty, and inequality. However, policies can go a long way toward alleviating suffering and fostering an inclusive recovery. The adverse output effects are limited for countries that provided relatively greater fiscal support. The increases in unemployment, poverty, and inequality are likewise lower for countries with relatively greater fiscal support and relatively stronger initial conditions (as defined by higher formality, family benefits, and health spending per capita).